Intensive Management of Postoperative Septic Shock in Patient with Secundum Atrial Septal Defect: A Case Report - Liliriawati Ananta Kahar; Wiwi Monika Sari; Rizki Oktavian (HM Publisher, 2023)
Background: Sepsis is a life-threatening organ dysfunction caused by an abnormal inflammatory response to infection. This study aimed to describe the intensive management of postoperative septic shock in secundum atrial septal defect patients. Case presentation: A 28-year-old woman complaining of pus discharge and reddish swelling in the scar after a cesarean section operation. The patient has a history of pulmonary hypertension and secundum ASD. While in the ICU, examination of vital signs found the patient was weak, compost mentis conscious, blood pressure 80/55 mmHG (MAP 63), Respiration 28 times per minute, pulse 114 times per minute, temperature 38.6°C with 98% oxygen saturation with NRM 10 L/ and laboratory examinations obtained hemoglobin 8.6, leukocytes 14.870, platelets 236.000, hematocrit 24, albumin 2.4 and procalcitonin > 100. Conclusion: This study reported that septic shock is a life-threatening condition, especially in patients with congenital heart disease. Appropriate, rapid, and comprehensive treatment and addressing the source of infection are essential in managing sepsis shock.